Cultural importance of flora for folk culture specialists in Cedral and Corazón de Jesús. Buffer zone, Alberto Manuel Brenes Biological Reserve - Jorquera García, Ada Luz (2019)
Ethnobotanical research has acquired significance due to the accelerated loss of traditional knowledge and the decrease of useful species as a consequence of natural habitat degradation. This research rescues the ethnobotanical knowledge of popular specialists and identifies the plants with the highest cultural importance in two communities from the buffer zone of the Alberto Manuel Brenes Biological Reserve. The qualitative ethnobotanical research was conducted with folk culture specialists through the application of in-depth interviews, free lists and ethnobotanical walks. The Cultural Importance Index allowed the identification of the most relevant species for these communities. The use of 214 species or taxonomic groups from 75 botanical families was recorded. The family with the largest number of useful species, Asteraceae, includes mainly herbaceous species used as a medicinal resource, followed by Orchids (Orchidaceae) used to decorate the exteriors of houses or gardens. The most important cultural species was Ciprés, Cupressus lusitanica, with multiple uses and secondly, the medicinal plants Neurolaena lobata (Gavilana), Chenopodium acuminatum (Apazote), Salvia rosmarinus and the multi-use tree Acnistus arborescens (Güitite).